ANALISIS KUALITAS SINYAL PADA JARINGAN LONG TERM EVOLUTION (LTE) MENGGUNAKAN DATA DRIVE TEST CLUSTER - Mardika, I Wayan; Sukadarmika, Gede; Sudiarta, Pande Ketut (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
The rapid development of cellular communication technology is inseparable from various problems especially on signal quality. In outdoor areas, the performance of eNodeB that is not optimal may cause communication failure. This research was conducted with the drive test on the L_BUNDARANRENON_PL, L_AKABA_PL and L_MYAMIN_CR to obtain signal quality parameters at Renon cluster area. The results of the drive test obtained compared to the simulation using the Atoll radio planning software with the Hatta Cost-231 propagation model and the Standard Propagation Model. From the comparison results, the margin value is used as a correction factor. The comparison results obtained based on the quality of SINR, The result of using the Standard Propagation Model is closer to the drive test measurement results than using Cost-231 Hatta. However, based on the quality of RSRQ, both propagation models yield almost the same results. Here are found that the correction factor for SINR obtained the Cost-231 Hatta propagation model of 6.15 dB and the Standard Propagation Model model of 6.11 dB. While for RSRQ correction factor the margin for both propagation models is -2 dB